2012
DOI: 10.1111/j.1756-185x.2012.01820.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of angiotensin converting enzyme insertion/deletion gene polymorphism among an Egyptian cohort of patients with rheumatoid arthritis

Abstract: Our study suggests that high frequency of the ACE D allele contributes to the heritability of RA susceptibility compared to other ACE alleles. On the other hand, no association was detected between ACE I/D polymorphism and the severity of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Therefore, we speculated that there may be an alternative inflammatory pathway through bradykinin activation in patients with AS. This speculation is also consistent with the results of various studies which suggested ACE inhibition for therapeutic effects in human inflammatory arthritis [12] and also a role for this enzyme in the pathophysiology of RA [35]. I allele of the ACE I/D polymorphism was found to be related to radiographically severe form of osteoarthritis and poor function.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Therefore, we speculated that there may be an alternative inflammatory pathway through bradykinin activation in patients with AS. This speculation is also consistent with the results of various studies which suggested ACE inhibition for therapeutic effects in human inflammatory arthritis [12] and also a role for this enzyme in the pathophysiology of RA [35]. I allele of the ACE I/D polymorphism was found to be related to radiographically severe form of osteoarthritis and poor function.…”
Section: Discussionsupporting
confidence: 80%
“…This relationship suggests a link between disease severity of osteoarthritis and I allele; however, there were no significant relationships between the distribution of genotypes and alleles of the ACE I/D polymorphism and susceptibility of knee osteoarthritis [14]. No relationships between disease severity and ACE ID genotypes' and alleles' distribution and RA patients were also reported [35]. Conversely, we found significant relationships between I allele of the ACE I/D polymorphism and susceptibility of AS.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…However, stimulation of AT2R has physiological effects opposite to stimulation of AT1R, such as vasodilation, inhibition of infl ammatory response, anti-fi brosis, and promotion of neuronal repair and regeneration (8)(9)(10)(11). Study showed that Ang II, AT1R, AT2R iNOS and TGM2 were signifi cantly increased in rheumatoid arthritis (RA), but AT1R was more signifi cantly increased than AT2R (12). The ratio of AT1R to AT2R was signifi cantly increased which has broken the original balance of AT1R/AT2R.…”
Section: Introductionmentioning
confidence: 99%